Review of Thomas Gallant's The Edinburgh History of the Greeks, 1768 to 1913: The Long Nineteenth Century - Zanou, Konstantina (Historein, 2015)
Review of Thomas W. Gallant, The Edinburgh History of the Greeks, 1768 to 1913: The Long Nineteenth Century, Edinburgh: Edinburgh University Press, 2015, viii + 372 pp